Effect of current, time, concentration of tin (II) chloride, and temperature on making tin powder using the electrodeposition - Oktanova, Riska; Oediyani, Soesaptri; Milandia, Anistasia; Subagja, Rudi (Jurnal Teknika, 2025)
The process of assembling electronic components into electronic equipment requires tin solder material. Tin solder in the form of paste is used to provide good contact between electronic components and PCB (Printed Circuit Board). To make tin solder paste, tin powder with a size of 15 to 50 microns is required. The development of efficient technology to produce tin powder with controlled characteristics from tin bar raw material is an important challenge to increase the added value of this commodity. This study was conducted to make tin metal powder from tin metal bars by electrodeposition using a chloride electrolyte solution containing tin ions. The experimental variables observed were the current density of the electrodeposition process (0,5-1,1 A/m²), the concentration of tin in the electrolyte solution (5-30g/l), and the temperature of the electrodeposition process (30-60°C). The experimental variables were observed for their effect on the size of the tin powder particles formed and the current efficiency of the tin powder formation process on the cathode surface. The results showed the highest current efficiency (75%) at a current of 0,5 A/m², a time of 15 minutes, and a temperature of 30°C. The tin powder had an irregular morphology, with a more uniform particle size at higher currents. SEM-EDS analysis showed a complex morphology with increasing temperature and deposition time. This process produced tin powder with a purity of up to 99%, the highest (99,4%) at a temperature of 50°C.